Fecal Calprotectin: A Screening Marker for the Early Detection of Necrotizing Enterocolitis among Children in Egypt - Ayman Emil Eskander; Rania Hosni Tomerak; Mona Safwat; Carolyne Ghobrial; Mohammad Nabih Almohammady; Walaa Abdelfattah (Mashhad University of Medical Sciences, 2020)
Background: Necrotizing enterocolitis (NEC) is a lethal disease affecting newborns with significant morbidity and mortality rates. Moreover, it is the most eminent gastrointestinal threat affecting premature newborns. Unfortunately, early symptoms and signs are usually vague; therefore, there is a special demand for sensitive biomarkers in this regard. This study aimed to investigate the role of fecal calprotectin in stage I NEC and identify specific cut off value at this stage to differentiate stage I NEC from other gastrointestinal disorders. Methods: This cross-sectional study was conducted at New Children Hospital, Cairo University, Egypt. In total, 100 newborns were included in this study who were assigned to the patient group with stage I NEC (n=60) and control group (n=40)with age and gender-matched newborns.Fecal calprotectin level was assessed using an enzyme-linked immunosorbent assay in both groups. Follow up of the patient group was performed for the development of stage II or III NEC. Results: The patient group obtained significantly elevated levels of fecal calprotectin, compared to the control group (P=0.000). Within the patient group, 43 (71.66%) newborns developed stage II or III NEC, whereas 17 (28.33%) cases developed no NEC. In addition, the level of fecal calprotectin was significantly higher in the group who developed stage II or III NEC (P=0.001). According to the receiver operating characteristic (ROC) curve, the cutoff value of 109.5 μg/g feces showed 100% sensitivity and specificity, and the area under the ROC curvewas equal to 1 in differentiating NEC from other conditions. Conclusion: The study showed that fecal calprotectin can be used as a sensitive and specific marker for the early detection of necrotizing enterocolitis.